Polymerization shrinkage of bulk fill composites and its correlation with bond strength - Almeida Junior, Lauber Jose dos Santos; Lula, Estevam Carlos de Oliveira; Penha, Karla Janilee de Souza; Correia, Vinicius Souza; Magalhães, Fernando Augusto Cintra [UNESP]; Lima, Darlon Martins; Firoozmand, Leily Macedo (FapUNIFESP (SciELO), 2018)
The present study aimed to evaluates polymerization shrinkage (PS) using microcomputed tomography (μCT) and microtensile bond strength (μTBS) in bulk fill composites (BFC) and conventional class I restorations as well as the correlation between these factors. Class I cavities (4 × 5 × 4 mm), factor-C = 4.2, were created in third molars that were free of caries, which were randomly divided in 4 groups (n = 6): XTI (Filtek Supreme XTE: incremental technique); XTB (Filtek Supreme XTE: single fill technique); TBF (Tetric Bulk Fill); and SF (SonicFill). Each tooth was scanned twice in μCT: T0 was after filling the cavity with composite, and T1 was after light curing. The data were analyzed by subtracting the composite volume for each time (T1-T0). After 1 week, the teeth were sectioned crosswise in the buccolingual and mesiodistal directions to obtain specimens with approximately 1 mm² thickness and fixed in a universal testing machine to perform μTBS. The Kruskal-Wallis and Dunn tests showed a statistically significant difference for shrinkage in µCT among the XTI and XTB and between the SF and XTB. Regarding the μTBS, all the groups differed from XTB. Bulk fill composites type presents a PS similar to that of the conventional nanoparticulate composite inserted using the incremental technique, but the bond strength was higher for the incremental group, which presented a lower number of pre-test failures when compared to BFC. No correlation was observed between the polymerization shrinkage and bond strength in the studied composites.
Keywords: Composite resins; Polymerization; Tensile strength; X-ray microtomography